Eutanasia Ditinjau dari Etika Kedokteran di Indonesia - Octaviane K. Rarung; Djemi Tomuka; James F. Siwu (Universitas Sam Ratulangi, 2024)
Abstract: Legal perspective euthanasia is a form of taking one's life. There are differences in the legality of euthanasia in Indonesia and several other countries that require doctors to understand the medical ethics related to euthanasia. This study aimed to explore the medical ethics related to euthanasia. This was a systematic literature review study using three database sources, namely ClinicalKey, Pubmed, and Sage Journal based on inclusion criteria and exclusion criteria. The results showed that euthanasia was not an appropriate and ethical matter for doctors to do. Doctors had to fulfill the autonomy of patients meanwhile doctors had also to consider the decisions given by patients since not all decisions of the patients had to be fulfilled, let alone decisions asking for euthanasia. Medical ethics viewed euthanasia as an unethical act to be performed by a doctor. Legal and religious views viewed euthanasia as something that should not be done. Moreover, medical ethics' view on euthanasia was different from bioethics' view on euthanasia. Bioethics viewed euthanasia from various perspectives, broader than medical ethics did. In conclusion, medical ethics respects the autonomy of the patient, albeit, the patient does not have the right to assert the obligation of others to fulfill that right. Keywords: euthanasia; medical ethics; doctors; patient’s autonomy Abstrak: Dalam perspektif hukum eutanasia merupakan suatu bentuk tindakan menghilangkan nyawa seseorang. Terdapat perbedaan legalitas eutanasia di Indonesia dengan beberapa negara lain yang mewajibkan dokter untuk mengetahui etika kedokteran terkait eutanasia. Penelitian ini bertujuan untuk memahami etika kedokteran terkait eutanasia. Jenis penelitian yang dilakukan ialah systematic literature review dengan tiga sumber database yang digunakan yakni ClinicalKey, Pubmed, dan Sage Journal berdasarkan kriteria inklusi serta kriteria eksklusi. Hasil penelitian mendapatkan bahwa eutanasia bukan hal yang pantas dan bukan hal yang etis untuk dilakukan oleh seorang dokter. Dokter memang harus memenuhi otonomi pasien namun dokter juga harus mempertimbangkan keputusan yang diberikan pasien karena tidak semua keputusan yang diambil pasien harus dipenuhi oleh dokter, apalagi keputusan meminta untuk eutanasia. Etika kedokteran memandang eutanasia sebagai tindakan yang tidak etis untuk dilakukan oleh seorang dokter. Pandangan hukum dan pandangan agama memandang eutanasia sebagai hal yang tidak patut untuk dilakukan. Pandangan etika kedokteran terhadap eutanasia berbeda dengan pandangan bioetika terhadap eutanasia. Bioetika memandang eutanasia dari berbagai sudut pandang, yang lebih luas dari pandangan etika kedokteran. Simpulan penelitian ini ialah etika kedokteran menghargai otonomi pasien namun pasien tidak mempunyai hak untuk menuntut kewajiban orang lain untuk memenuhi hak tersebut. Kata kunci: eutanasia; etika kedokteran; dokter; otonomi pasien